2020
DOI: 10.1109/access.2019.2959235
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Estimator for TDOA and FDOA Positioning of Multiple Disjoint Sources in the Presence of Calibration Emitters

Abstract: Multiple-target localization is extensively applied in wireless connected networks. However, sensor location uncertainty is known to degrade significantly the target localization accuracy. Fortunately, calibration emitters such as unmanned aerial vehicles (UAV) with known location can be used to reduce the loss in localization accuracy due to sensor location errors. This paper is devoted to the use of UAV calibration emitters for time differences of arrival (TDOA) and frequency differences of arrival (FDOA) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The simulation results demonstrated that the proposed algorithm could produce the optimal solution to the formulated constrained WLS problem. Additionally, its estimation RMSE can achieve CRLB with calibration emitters at common noise; from that, the analytical validation results verified that the proposed algorithm is better than some existing localization algorithms [90]. In [91], a simple algorithm is designed for movable target estimation using three or more stationary sensors.…”
Section: Weighted Least Square (Wls)mentioning
confidence: 70%
See 1 more Smart Citation
“…The simulation results demonstrated that the proposed algorithm could produce the optimal solution to the formulated constrained WLS problem. Additionally, its estimation RMSE can achieve CRLB with calibration emitters at common noise; from that, the analytical validation results verified that the proposed algorithm is better than some existing localization algorithms [90]. In [91], a simple algorithm is designed for movable target estimation using three or more stationary sensors.…”
Section: Weighted Least Square (Wls)mentioning
confidence: 70%
“…In the first stage, the location of the sensors is enhanced based on the calibration measurements as well as the previous knowledge of the sensors position. In the second stage, the estimate of the multiple target geolocation is obtained by joining the measurements of emitted signals and the estimated values obtained in the first stage [90]. The simulation results demonstrated that the proposed algorithm could produce the optimal solution to the formulated constrained WLS problem.…”
Section: Weighted Least Square (Wls)mentioning
confidence: 97%
“…Mobility and the lack of spatial restrictions in the UAV missions is a special property that determines the use of these vehicles both to create dynamically changing network structures and the implementation of additional communications services such as the location of emission sources. The prospects for using the UAVs to improve the quality and scope extension of communication services in fifth-generation (5G) mobile networks and in the localization systems of fixed emission sources are presented in [10,11] and [12], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Time and frequency differences of arrival (TDOAs and FDOAs) measurements performed by many sensors are some of the more commonly used techniques for estimating the position of mobile emitters [12][13][14][15]. Target tracking techniques based on the TDOA measurements in a WSN are described, i.a., in [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Close in meaning to ToF is the algorithm ToA (Time of Arrival), which is based on distance calculation by measuring the signal transit time from the mobile terminal to the base station as the difference between the time the signal was sent and received [ 21 , 22 , 23 , 24 ]. The algorithm ToA is often used with TDoA (Time Difference of Arrival) [ 25 ] and FDoA (Frequency difference of arrival) [ 26 ], which are also often used together [ 27 , 28 , 29 , 30 ]. TDoA is a very popular algorithm for different applications and measures the difference in the time of arrival of a signal from an object to several base stations [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%